Collection, Storage, and Preparation of Human Blood Cells. Issue 1 (1st July 2015) - Dagur, Pradeep K.; McCoy, J. Philip
Abstract: Human peripheral blood is often studied by flow cytometry in both the research and clinical laboratories. The methods for collection, storage, and preparation of peripheral blood will vary depending on the cell lineage to be examined as well as the type of assay to be performed. This unit presents protocols for collection of blood, separation of leukocytes from whole blood by lysis of erythrocytes, isolating mononuclear cells by density gradient separation, and assorted non‐flow sorting methods, such as magnetic bead separations, for enriching specific cell populations, including monocytes, T lymphocytes, B lymphocytes, neutrophils, and platelets, prior to flow cytometric analysis. A protocol is also offered for cryopreservation of cells, since clinical research often involves retrospective flow cytometric analysis of samples stored over a period of months or years. © 2015 by John Wiley & Sons, Inc.